2012
DOI: 10.1097/brs.0b013e3182512425
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of the Intact and Destabilized Sheep Cervical Spine

Abstract: The sheep cervical spine is extremely flexible, as seen by the large range of motion and neutral zone. The large neutral zone may account for the coupled motion between axial rotation and lateral bending. The facets and capsular ligaments provide significant stability, especially in axial rotation, flexion, and extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…While much has been reported about the strength of the capsular ligaments as related to cervical stability, when damaged, these ligaments lose their strength and are unable to support the cervical spine properly. For instance, in an animal study, it was shown that sequential removal of sheep capsular ligaments and cervical facets caused an undue increase in range of motion, especially in axial rotation, flexion and extension with caudal progression [ 31 ]. Human cadaver studies have also indicated that transection or injury of joint capsular ligaments significantly increases axial rotation and lateral flexion [ 32 , 33 ].…”
Section: Cervical Capsular Ligamentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While much has been reported about the strength of the capsular ligaments as related to cervical stability, when damaged, these ligaments lose their strength and are unable to support the cervical spine properly. For instance, in an animal study, it was shown that sequential removal of sheep capsular ligaments and cervical facets caused an undue increase in range of motion, especially in axial rotation, flexion and extension with caudal progression [ 31 ]. Human cadaver studies have also indicated that transection or injury of joint capsular ligaments significantly increases axial rotation and lateral flexion [ 32 , 33 ].…”
Section: Cervical Capsular Ligamentsmentioning
confidence: 99%
“…Animal models used for initiating disc degeneration in research studies have shown the induction of spinal instability through injury of the facet joints [ 68 , 69 ]. In similar models, capsular ligament injuries of the facet joints caused multidirectional instability of the cervical spine, greatly increasing axial rotation motion correlating with cervical disc injuries [ 31 , 28 , 70 , 71 ]. Using human specimens, surgical procedures such as discectomy have been shown to cause an immediate increase in motion of the segments involved [ 72 ].…”
Section: Cervical Spondylosis: the Instability Connectionmentioning
confidence: 99%
“…3a) was employed to provide the specified loading and motion, simulating those of the natural spine with a maximum load magnitude of 4.5 kN along the Z direction, a maximum flexion angle of ± 100°along the X direction, a maximum abduction angle of ± 30°along the Y direction, and a maximum rotational motion of ± 40°. According to the set-up of the intact SCS model, the load of a bending moment of 2.5 Nm was applied towards the X+ direction at a rate of 5.0 Nm/min until up to 2.5 Nm (DeVries et al 2012) to simulate lateral bending in response to the X+ motion of the spine. Under such a loading environment, the C3-C4 vertebral body specimens were forced to bend laterally and then fully recovered their natural posture when the loading system was withdrawn.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…In particular, we report the results of measurements of the normal flexion/extension and rotational movements of the cervical and upper thoracic spine made on a series of adult sheep, each implanted with a prototype HSCMS device. A quantitative assessment of the range and rate of their routine behavioural motions demonstrates that this largeanimal model constitutes a type of natural accelerated stress cycling-platform for the in situ evaluation of stimulator lead robustness and provides further support for the utility of the ovine model in studies of spinal biomechanics [14][15][16].…”
Section: Introductionmentioning
confidence: 98%